Currency Risk Management Practices in India - An Evidence from the Textile Sector - Basanna, Prakash; Pundareeka Vittala, K. R. (Indian Journal of Research in Capital Markets, 2019)
Currency risk management involves using external techniques such as forwards, futures, options, and swaps, which are called as currency derivatives in addition to internal techniques. The firms with greater growth opportunities and tighter financial constraints are more inclined to use currency derivatives. The forex market provides various derivative instruments to hedge against currency exposures such as currency forwards, options, futures, and swaps. The current paper aimed at studying various external hedging techniques used in India for managing currency exposure. For this purpose, foreign exchange cash flows arising out of imports and exports and exchange gain/losses of nine sample companies chosen from the textile sector were used. It was observed from the study that only two currencies: USD and EUR held command in the forex market and other currencies were used minimally. It was also noted that there were several currency derivatives available to the business firms such as forwards, futures, options, swaps, etc. for hedging currency exposure. However, among all these techniques, forward contract was considered to be an effective and widely used hedging tool, which was followed by currency swap, options, and futures.